2003
DOI: 10.1007/bf02478943
|View full text |Cite
|
Sign up to set email alerts
|

Malignant transformation of meningeal melanocytoma: A case report

Abstract: Intracranial meningeal melanocytoma is an uncommon tumor that is considered benign. We formerly reported an intracranial meningeal melanocytoma. Here we report a extremely rare case of malignant transformation of this tumor. A 49-year-old man complained of a headache. Magnetic resonance scanning revealed a mass in the left frontal region. The patient underwent gross total removal of the tomor in 1994. The histological findings showed a meningeal melanocytoma. In 1998, he underwent gamma-knife surgery for local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 23 publications
0
46
0
5
Order By: Relevance
“…Especially in case of incomplete resection, melanocytomas frequently recur (up to 50% recurrence reported 1 year after surgery) (108). Also, aggressive behavior with leptomeningeal seeding or rarely malignant transformation into melanoma has been reported (20,72,108,132). Whenever possible, melanocytomas should be completely resected.…”
Section: Melanocytomamentioning
confidence: 97%
“…Especially in case of incomplete resection, melanocytomas frequently recur (up to 50% recurrence reported 1 year after surgery) (108). Also, aggressive behavior with leptomeningeal seeding or rarely malignant transformation into melanoma has been reported (20,72,108,132). Whenever possible, melanocytomas should be completely resected.…”
Section: Melanocytomamentioning
confidence: 97%
“…Two separate biopsies were thought to contain only benign melanocytoma cells and the enucleated eye contained residual melanocytoma-like cells, so it is conceivable that de-differentiation to melanoma had occurred over time, or that the initial samples had missed a deeper small ciliary-body lesion. Malignant transition from melanocytoma of the optic disc,3 4 choroid,5 6 ciliary body7 and meninges8 has been described, but malignant transformation of iris melanocytoma was not found in one series at 5 years 1. However, Cialdini et al 2 reported a discrete, rather than ring configuration, iris tumour that contained malignant and melanocytoma cells.…”
Section: Commentmentioning
confidence: 99%
“…Radiation therapy is reserved for cases in which complete resection is not possible or in which there is a recurrence(40). There have been reports of melanocytomas transforming into malignant melanoma, spreading along the leptomeninges, and even demonstrating distant metastasis(34,(41)(42)(43).…”
mentioning
confidence: 99%